Degenerative outcomes of digital identity platforms for development. (7th June 2021) - Masiero, Silvia; Arvidsson, Viktor
Abstract: Digital identity platforms are widely regarded as important means to improve social protection systems. Yet these platforms have been implicated in the production of a range of unintended outcomes for development beneficiaries. To clarify how digital identity platforms enable the production of one such outcome that we call degenerative, because it causes target systems to deteriorate, we conduct a case study of the incorporation of Aadhaar, the world's largest digital identity platform, in India's primary food security scheme. Based on the data from two South Indian states, we show how the incorporation produced degenerative effects in the access, monitoring, and policy layers of the social protection system. These effects lead us to theorise how Aadhaar enabled the degenerative outcome via exclusion, distortion, and redirection, making public distribution of subsidised goods displaceable in favour of cash transfers.